The influence of pressure on crude oil biodegradation in shallow and deep Gulf of Mexico sediments. - Uyen T Nguyen; Sara A Lincoln; Ana Gabriela Valladares Juárez; Martina Schedler; Jennifer L Macalady; Rudolf Müller; Katherine H Freeman (PLoS ONE)
A significant portion of oil released during the Deepwater Horizon disaster reached the Gulf of Mexico (GOM) seafloor. Predicting the long-term fate of this oil is hindered by a lack of data about the combined influences of pressure, temperature, and sediment composition on microbial hydrocarbon remineralization in deep-sea sediments. To investigate crude oil biodegradation by native GOM microbial communities, we incubated core-top sediments from 13 GOM sites at water depths from 60-1500 m with crude oil under simulated aerobic seafloor conditions. Biodegradation occurred in all samples and followed a predictable compound class sequence dictated by molecular weight and structure. 45 to ~100% of total n-alkane and 3 to 60% of total polycyclic aromatic hydrocarbons (PAH) were depleted. In reactors incubated at 4°C and at pressures of 6-15 MPa, the depletion in total n-alkane was inversely correlated to pressure (R2 ~ 0.85), equivalent to a 4% decrease in total n-alkane depletion for every 1 MPa increase. Our results indicated a modest inhibitory effect of pressure on biodegradation over our experimental range. However, the expansion of oil exploration to deeper waters (e.g., 5000 m) opens the risk of spills at conditions at which pressure might have a more pronounced effect.